2005
DOI: 10.1007/s00277-005-1026-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea in thalassemia intermedia—a promising therapy

Abstract: Pharmacological agents such as hydroxyurea (HU) have been known to cause induction of fetal hemoglobin and possibly may alleviate the symptoms in thalassemia intermedia patients. Thirty-seven patients with beta-thalassemia intermedia were enrolled to assess response to HU therapy. Major response was defined as transfusion independence or hemoglobin rise of more than 20 g/l and minor response as rise in hemoglobin of 10-20 g/l or reduction in transfusion frequency by 50%. The median age was 10 years (range: 4-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 14 publications
9
74
0
3
Order By: Relevance
“…HU is the most used HbF inducer in both moderate to severe forms of β-thalassaemia. More than 500 patients with β-thalassemia have been treated with HU worldwide and about 50% of them responded to the treatment, exhibiting a clear amelioration of the clinical parameters (22,29,(38)(39)(40). Other inducers of HbF synthesis, such as butyrate, 5-azacytidine and more recently, decitabine, have also been employed, however, these HbF inducers have shown only a modest response in the majority of β-thalassemia patients as well as some degree of toxicity (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HU is the most used HbF inducer in both moderate to severe forms of β-thalassaemia. More than 500 patients with β-thalassemia have been treated with HU worldwide and about 50% of them responded to the treatment, exhibiting a clear amelioration of the clinical parameters (22,29,(38)(39)(40). Other inducers of HbF synthesis, such as butyrate, 5-azacytidine and more recently, decitabine, have also been employed, however, these HbF inducers have shown only a modest response in the majority of β-thalassemia patients as well as some degree of toxicity (22).…”
Section: Discussionmentioning
confidence: 99%
“…HU and butyrate analogues are the most studied compound (22). For example, Dixit et al (38) reported the results of treatment with HU of 37 patients with β-thalassemia intermedia. After a median follow-up of 12 months, 26 patients (70.2%) responded: 45.9% were major responders (transfusion independence or >20 g/l increase in Hb) and 24.3% were minor responders (a 50% reduction in transfusion frequency or a 10-20 g/l increase in Hb) (22,29).…”
Section: Resveratrol: Antioxidant Activity and Induction Of Fetal Hemmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Hydroxyurea (HU) is FDA approved for treatment of SCD patients and it is also widely used for β-thalassemia. [8][9][10][11][12] How HU induces HbF production is poorly understood. Mechanisms proposed for the induction of HbF by HU include rapid erythroid regeneration, increased erythropoietin (EPO) production, apoptosis, nitric oxide (NO) production, 13 increased guanylate cyclase activity 13 and activation of the p38 MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have been confirmed in large studies carried out on Iranian, Indian, and Algerian β-thalassemic patients, showing good responses in a significant proportion (i.e., >50%) of β-thalassemic patients, without any major toxicity related to HU administration [194][195][196][197][198][199][200].…”
Section: Butyratementioning
confidence: 60%